Linosa island: a unique heritage of Mediterranean biodiversity - Sara Innangi; Luciana Ferraro; Michele Innangi; Gabriella Di Martino; Laura Giordano; Valentina Alice Bracchi; Renato Tonielli (Journal of Maps)
This publication presents a newly created map of the seafloor of Linosa, a volcanic island located in the Sicily Channel (Mediterranean Sea). The seafloor of Linosa was previously surveyed using geophysical and ground-truth data (in 2016 and 2017). Linosa is regarded as a "sentinel area" for alien species and worldwide environmental changes because of its geographical location, making it worthy of particular attention. The predominant habitats found in Linosa have been identified as three priority habitats: Posidonia oceanica meadows, rhodolith beds, and coralligenous habitats, which encompass extensive coral forests. Another crucial environmental indicator is the assemblages of benthic foraminifera, which were previously studied in this area to analyse their correlations with the topography of the seafloor. Hence, all the accessible data was gathered to create a novel comprehensive map of the seabed (at a scale of 1:15,000), with the objective of displaying and highlighting the abundant marine biodiversity of Linosa.